Civilizing rituals : inside public art museums - Duncan, Carol (London ; : Routledge, 1995)
From the princely gallery to the public art museum: the Louvre Museum and the National Gallery, London -- Public spaces, private interests: municipal art museums in New York and Chicago -- Something eternal: the Donor Memorial -- The modern art museum: it's a man's world.
CCS Gent
Includes bibliographical references (p. 162-173) and index.
boek
Keywords: Art museums -- Social aspects; Art museum attendence